RADIKALISME ISLAM DAN ANCAMAN KEBANGSAAN - Robingatun Robingatun (IAIN Kediri, 2017)
This article involves analyzing about the ideology and practices of Indonesia radical organizations and its correlation to the future of Indonesian unity. The goal of this research tries to prove that the practices and ideology of radicalism is so danger for the Indonesian future. By analyzing several data and phenomenon in the news, report, books and the story of this radicalism group this research will be conducted. This research is a literature review of several books, journals and theories about radicalism in Indonesia. In conclusion, this article invites all of element of govermance, institution, academic institution and civil society to minimize the movement of radicalism in Indonesia. Key words: Radicalism, Islam, Violence